(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2024)
This article discusses certain characteristics of the leader characters portrayed in Abdulla Qodiriy’s novel O‘tkan Kunlar.